2016
DOI: 10.1186/s13018-016-0458-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the surgical torque limiter: a model comparing drill- and hand-based screw insertion into locking plates

Abstract: BackgroundThe objective of this study is to analyse the effectiveness of the surgical torque limiter during operative use. The study also investigates the potential differences in torque between hand and drill-based screw insertion into locking plates using a standardised torque limiter.MethodsTorque for both hand and power screw insertion was measured through a load cell, registering 6.66 points per second. This was performed in a controlled environment using synthetic bone, a locking plate and locking screws… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…For example, for 3.5 mm nominal thread diameter cortical screws, the minimum breaking torque is estimated at 2300 N•mm. Similarly, for 4.0 mm nominal threaded diameter cancellous screws, the minimum breaking torque is 1300 N•mm, while for 3.5 mm nominal threaded diameter locking screws, it is 1500 N•mm [31]. The FE simulations in this study showed that the maximum torque to failure for some cases was lower than the standard values specified by ISO 6475 (Figure 4).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For example, for 3.5 mm nominal thread diameter cortical screws, the minimum breaking torque is estimated at 2300 N•mm. Similarly, for 4.0 mm nominal threaded diameter cancellous screws, the minimum breaking torque is 1300 N•mm, while for 3.5 mm nominal threaded diameter locking screws, it is 1500 N•mm [31]. The FE simulations in this study showed that the maximum torque to failure for some cases was lower than the standard values specified by ISO 6475 (Figure 4).…”
Section: Discussionmentioning
confidence: 53%
“…In accordance with ISO 6475, the minimum breaking torque values are established for different types of screws based on the nominal thread diameter [31]. For example, for 3.5 mm nominal thread diameter cortical screws, the minimum breaking torque is estimated at 2300 N•mm.…”
Section: Discussionmentioning
confidence: 99%
“…During the internal fixation procedures, after all implants had been placed, the screws need to be tightened at the end of the procedure to ensure primary stability has been achieved. Several studies have shown a difference between the torque exhibited by different surgeons ( 39 , 40 ). However, insertional torque in locking plates is related to the screw and plate interface and satisfactory torque is achieved when the screw head fully engages the plate and can no longer be advanced.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is effective at preventing overtightening but does little to ensure a minimum torque. Torque-limiting devices exist for some cases [9], especially in orthodontics, which uses small screws with low torque values [10], but these still require the surgeon to know and select the correct torque or limiter manually, in contrast to the proposed automatic model-based method.…”
Section: Introductionmentioning
confidence: 99%